Irresolvable left topological groups - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove that an irresolvable left topological group is of the first category. The pseudocharacter of an irresolvable left topological groupG is countable, provided thatG is Abelian or its cardinality is nonmeasurable. Some other cardinal invariants of an irresolvable left topological group are also determined.